2019
DOI: 10.22146/jntt.42966
|View full text |Cite
|
Sign up to set email alerts
|

Deteksi Penyakit Zoonosis Ehrlichiosis pada Pasien Anjing di Klinik Hewan Jogja

Abstract: Ehrlichiosis is a zoonotic diseases caused by blood parasitic infection that can be transmitted by a ticks. Dogs infected with Ehrlichiosis canis who not treated for long periods of time can cause anemia and result in death. Although many diseases are found in the field but the percentage rate of the incidence of the disease is unknown. This study aims to detect Ehrlichiosis disease in dog patients treated at Jogja Veteinary Clinic by using Ehrlichiosis diagnosis kit available in the field. The materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Uji serologi merupakan salah satu uji yang dapat digunakan untuk memastikan diagnosis ehrlichiosis pada anjing (Nakaghi et al, 2008). Namun, perlu digaris bawahi bahwa penggunaan rapid test kit bisa saja menunjukkan hasil negatif ketika hewan berada pada fase akut penyakit, dimana fase akut ehrlichiosis ini berlangsung selama 7 sampai 14 hari (Nesti et al, 2018). pISSN: 2085-2495eISSN: 2477eISSN: -2712 Juni 2023 Online pada: http://ojs.unud.ac.id/index.php/buletinvet DOI: 10.24843/bulvet.2023.v15.i03.p17 Penanganan yang dilakukan terhadap anjing kasus yaitu dengan memulihkan kondisi anjing setelah penjahitan terhadap luka robek akibat gigitan anjing besar yaitu dengan pemberian infus NaCl 0,9% (Sodium Chloride 0,9%, PT Widatra Bhakti, Pasuruan, Jawa Timur) untuk menggantikan cairan tubuh yang hilang, menangani ketidakseimbangan elektrolit, dan menjaga tubuh agar tetap terhidrasi.…”
Section: Hasilunclassified
“…Uji serologi merupakan salah satu uji yang dapat digunakan untuk memastikan diagnosis ehrlichiosis pada anjing (Nakaghi et al, 2008). Namun, perlu digaris bawahi bahwa penggunaan rapid test kit bisa saja menunjukkan hasil negatif ketika hewan berada pada fase akut penyakit, dimana fase akut ehrlichiosis ini berlangsung selama 7 sampai 14 hari (Nesti et al, 2018). pISSN: 2085-2495eISSN: 2477eISSN: -2712 Juni 2023 Online pada: http://ojs.unud.ac.id/index.php/buletinvet DOI: 10.24843/bulvet.2023.v15.i03.p17 Penanganan yang dilakukan terhadap anjing kasus yaitu dengan memulihkan kondisi anjing setelah penjahitan terhadap luka robek akibat gigitan anjing besar yaitu dengan pemberian infus NaCl 0,9% (Sodium Chloride 0,9%, PT Widatra Bhakti, Pasuruan, Jawa Timur) untuk menggantikan cairan tubuh yang hilang, menangani ketidakseimbangan elektrolit, dan menjaga tubuh agar tetap terhidrasi.…”
Section: Hasilunclassified
“…chronic exposure of melamine, heavy metals, or organic compounds) may be attributed as the possible etiologies of early renal failure in this dog. Positive serological tests for Ehrlichia antibodies have been reported in multiple studies in Indonesian stray dogs (Bagus and Ardana 2017;Nesti et al 2019;Putra et al 2019), but further studies are imperative to determine the epidemiology of ehrlichiosis in Indonesian dogs to appropriately determine its risk factor. Serological testing for ehrlichiosis detection was not conducted in this dog, so this hypothesis is unproven.…”
Section: Pathophysiology Of Ckdmentioning
confidence: 99%
“…There was also a report of an ehrlichiosis case in a Kintamani dog in Bali based on history, clinical symptoms, routine hematological results, and examination using a test kit which showed that the dog was E. canis positive (Erawan et al 2017). Report on cases of ehrlichiosis disease detection in 1.785 dog patients at Jogja Animal Clinic using a kit test from January to September 2017 obtained a positive result of 7.63% (Nesti et al 2018).…”
Section: Introductionmentioning
confidence: 99%